Nezināmās lappuses latviešu mākslinieku dzīvē neatkarības karš 1918.-1920. gadā - Jēkabsons, Ēriks 1965- (2021)
From the summer of 1919, the Latvian War of Independence (1918–1920) and Provisional Government had the nation's relatively strong support. In the autumn of 1919, the German-Russian Western Russian volunteer army led by Pavel Bermondt was completely driven out of the territory of Latvia as was the Red Army of Soviet Russia in early 1920. Most of the Latvian population took part in the struggle for independence, and some of them were forced to stand in the ranks of opponents of Latvian statehood (Army of Soviet Latvia and Red Army of Soviet Russia) for some time, which was determined by the difficult military-political situation in the region and Latvia. Already during the First World War, most Latvian men in the age group suitable of military service were in the service of the Russian army. The new generation of Latvian artists formed a very specific and important, albeit relatively small contingent. In addition, during their military service in the Russian army and then in other armed formations, some of them continued to maintain active mutual contacts and, as far as possible, to engage in art. The aim of the article is to reflect the hitherto unknown pages in the life of Latvian artists during the Latvian War of Independence, when many of them directly participated in important yet insufficiently researched episodes of this important process. In this way, both the body of biographies of prominent artists (reflecting aspects of their lives that have been insufficiently researched for various reasons) and the understanding of the history of the War of Independence in general are significantly supplemented.